Puffer fish and its consumption: to eat or not to eat? - Panão, Inês (2015)
"This systematic review was done to examine the substantial increase in the number of intoxication cases in puffer fish associated with tetrodotoxin. In the past 5 years, 430 cases of intoxication and 52 deaths associated with puffer fish have been reported worldwide. It has also been verified that puffer fish have migrated to different regions, which has led to a negative environmental impact. Based on the information obtained herein, consumption of puffer fish should be legally limited, although it still remains very popular in several regions with negative social and economic impacts."